(untitled) (Literary Voice, 2024)
The present paper seeks to analyse two Indian trans autobiographies - The Truth About Me: A Hijra Life Story (2010) by A. Revathi, a distinguished trans activist; and Me Hijra, Me Laxmi (2015) by Laxmi Narayan Tripathi, a prominent Bharatnatyam dancer and trans activist. The autobiographical accounts critically explore the contribution of prevalent heteronormative ideologies to the marginalised status of transgender individuals in India. The narratives intricately depict the experiences of transgender individuals who grapple with a sense of mismatch between their assigned sex and psychological sex, ultimately leading them to undergo Sex Reassignment Surgery (SRS) and related medical procedures. Drawing upon the perspectives of post-transsexual scholars such as Jacques Juliet, Janice Raymond, Jay Prosser, Kate Bornstein, and Sandy Stone, the study asserts that the transgender body is "programmed to disappear," promotes a "denial of mixture," and perpetuates the "purity" of gender after the corporeal transition. Furthermore, the paper examines how trans individuals incorporate established medical discourse on transsexuality into their autobiographies. The research findings underscore the need to develop a transgender discourse capable of offering a counter-discourse to the binary explanations of gender.